Cloned genes and genetic regulation of anthocyanin biosynthesis in maize, a comparative review - Chachar, Zaid; Lai, RuiQiang; Ahmed, Nazir; Lingling, Ma; Chachar, Sadaruddin; Paker, Najeeba Parre; Qi, YongWen (Frontiers in Plant Science, 2024)
This review presents several novel contributions to the field of plant genetics and biotechnology particularly in relation to maize. This is the first study to provide comprehensive molecular mapping of all genes involved in anthocyanin biosynthesis in maize including the identification and cloning of functional alleles such as C1, C2, Pl1, Pl2, Sh2, ZmCOP1 and ZmHY5. Notably, this study establishes new interdisciplinary connections by linking the role of the Sh2 gene in sugar-to-starch conversion to anthocyanin synthesis thereby opening avenues for improving the nutritional content of maize. Additionally, this study uncovered a previously unexplored relationship between anthocyanin biosynthesis and plant photomorphogenesis through the key regulatory genes ZmCOP1 and ZmHY5.The advanced methodological approaches employed set a new standard for future research and the findings have far-reaching implications for global food security and health as they lay the groundwork for the development of genetically improved maize varieties with enhanced color traits and potential health benefits.